2021
DOI: 10.1111/aor.13993
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the Clearum dialyzer

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…Blood Purif DOI: 10.1159/000528983 than in HF which is to be replicated in fuanalysis of HDFit data [38,39,90].…”
Section: Post-dialysis Recovery Timementioning
confidence: 93%
“…Blood Purif DOI: 10.1159/000528983 than in HF which is to be replicated in fuanalysis of HDFit data [38,39,90].…”
Section: Post-dialysis Recovery Timementioning
confidence: 93%
“…The results of this study corroborate and extend those of Maduell, which assessed the dialyzer in short-term only; here, we support those by a novel in-vitro assay and add clinical medium-term data. 14…”
Section: Clearum Hs Hemodialyzer Sessionsmentioning
confidence: 99%
“…Fourteen (14) of the 20 patients (70%) previously used the high-flux Fresenius FX classix 100 dialyzer at baseline, while the remaining patients were using the FX classix 80 (n = 4) and FX classix 60 (n = 2), respectively. Average blood flow rates over the three months prior to the study ranged between 251-299 mL/min (n = 1), 300-349 mL/min (n = 9), and 350-400 mL/min (n = 10) in the enrolled patients.…”
Section: Demographic and Other Baseline Characteristicsmentioning
confidence: 99%
“…31,32 When post-HDF is prescribed, the dialyzer membrane should also be chosen with caution, because the performance of the different dialyzers varies, even when other dialysis parameters remain unchanged. 9,22,33,34 Studies comparing HDF with polyamide 25,26,35 and first-generation helixone 28 filters versus HDx obtained slightly inferior results compared with last-generation polysulfone filters. 8,9,22 The influence of the amount of convective volume in HDF seems to be decisive in achieving or enhancing the performance of HDx.…”
Section: Efficacy Comparison Of Hdf Versus Hdxmentioning
confidence: 99%
“…Post‐dilution online hemodiafiltration (post‐HDF) has progressively evolved and can be considered a safe, fully consolidated treatment with multiple clinical advantages 10 . The ESHOL study reported longer survival in patients receiving post‐HDF, 11 and post hoc analysis of three randomized clinical trials with mortality as the primary endpoint showed an association between convective volume and survival 11–13 . In this regard, obtaining a replacement volume greater than 21 L per session has been recommended to achieve this survival benefit 14 …”
Section: Introductionmentioning
confidence: 99%